Solution and solid state structures and magnetism of a series of linear trinuclear compounds with a hexacoordinate LnIII and two terminal NiII centers - Comba, Peter; Enders, Markus; Großhauser, Michael; Hiller, Markus; Müller, Dennis; Wadepohl, Hubert (Dalton transactions, 2017)
Reported are the syntheses, structures and magnetic properties, also by NMR spectroscopy in solution, of a series of 13 linear trinuclear 3d-4f compounds with a lanthanide(III) surrounded by two NiII ions, NiII2LnIII, where the central LnIII is hexacoordinate. For three of the crystal structures, an additional H2O molecule is coordinated to the central LnIII ion, leading to a monocapped trigonal prismatic structure. However, NMR spectroscopy indicates that in solution, these complexes also have a hexacoordinate LnIII center. The solution magnetic anisotropies, determined by NMR spectroscopy, indicate that the axial components of the anisotropies are relatively small and that the DyIII derivative might therefore not exhibit single molecule magnetism. The axial anisotropies determined by NMR spectroscopy are in good agreement with the expectations based on the distorted trigonal prismatic ligand field.
First published: 30 Nov 2016
Gesehen am 22.08.2018